2016
DOI: 10.1158/1078-0432.ccr-15-0589
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Trametinib and Palbociclib Radiosensitizes KRAS-Mutant Non–Small Cell Lung Cancers In Vitro and In Vivo

Abstract: Purpose: To investigate the potential roles that p16 (CDKN2A) and RB activation have in sensitization to MEK inhibitor in resistant KRAS-mutant non-small cell lung cancer cells (NSCLC) in vitro and in vivo.Experimental Design: Cell viability was measured with MTS assays. Effects of administration of radiation and combination drug treatments were evaluated by clonogenic assay, flow cytometry, and Western blots. DNA repair was assessed using immunofluorescent analysis. Finally, lung cancer xenografts were used t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 53 publications
7
56
0
Order By: Relevance
“…Delayed DNA double-strand break repair has recently been reported for irradiated KRASmutant non -small cell lung cancers that are cotreated with palbociclib and the MEK inhibitor trametinib. 28 Our findings, as well as the findings of others, suggest that palbociclib inhibits nonhomologous end-joining repair of double-strand breaks. Inhibition of double-strand break repair by palbociclib is most evident in tumor cells treated with palbociclib during and after irradiation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Delayed DNA double-strand break repair has recently been reported for irradiated KRASmutant non -small cell lung cancers that are cotreated with palbociclib and the MEK inhibitor trametinib. 28 Our findings, as well as the findings of others, suggest that palbociclib inhibits nonhomologous end-joining repair of double-strand breaks. Inhibition of double-strand break repair by palbociclib is most evident in tumor cells treated with palbociclib during and after irradiation.…”
Section: Discussionsupporting
confidence: 83%
“…Potential benefit from the use of palbociclib with RT has been shown in preclinical studies of noncentral nervous system cancer 28,29 as well as in preclinical studies of 2 other types of brain tumors that occur predominantly in the pediatric population (ie, medulloblastoma 30 and brainstem glioma 31 ). Our results build upon the observations of these studies-as well as our previous study of GBM 5 -by showing that the timing of palbociclib treatment relative to the administration of radiotherapy could prove important for maximizing the benefit from inhibiting CDK4/6 in association with RT.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] We analyzed the combinatorial effects of palbociclib with the commonly used chemotherapy agents against CRC, as a prelude to possible translation. Chou-Talalay analysis revealed that palbociclib can synergize with a variety of chemotherapies under hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 A combined pharmacological inhibition of MEK and CDK4/6 led to substantial synergy in KRAS-mutated NSCLC in vivo. 8 Synergy of palbociclib with a MEK inhibitor has also been demonstrated in KRAS mutant colon cancer in vivo. 9,10 Vemurafenib-resistant tumors remain sensitive to palbociclib suggesting that initial treatment with vemurafenib followed by palbociclib with or without mTOR inhibitors might provide an approach to overcome recurrence of vemurafenibresistant, metastatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are instances where it appears that the combinations result in a synthetic cytotoxic response. For example, the combination of MEK and CDK4/6 inhibitors in non-small cell lung cancer induces cell death in concert with cell cycle inhibition [112]. The exact mechanisms underlying each combinatorial sensitivity is likely conditioned by the underlying genetic features of the tumor, as the same drug combination can have differing effects based on the tumor model studied.…”
Section: Combination Therapiesmentioning
confidence: 99%